Feasibility Study on the Use of Fly Ash and Bottom Ash as Aggregate Substitutes in the Subbase Layer of Road Pavement - M Arief Firdaus; Rini Kusumawardani; Nirima Ramadhani; Zahra Aulia Putri (Universitas Negeri Semarang, 2024)
This study used fly ash and bottom ash (FABA) waste as a substitute for aggregate in the road subbase layer. The initial mixture included FABA with a depth of 1 meter and 7 meters without mixing other materials. This mixture is differentiated into two variations with a ratio of variation I (70:30) and variation II (70:30), each fermented for 14 days. The test results showed that the FABA material did not meet the specification of SNI 6388:2015 for class B foundation layers, with a maximum immersion CBR value of 25.32% in variation I and 18.99% in variation II. This study evaluates the feasibility of using FABA as an aggregate substitute material in the subbase layer of road pavement. From the results obtained, FABA material has the potential to be used in subbase construction. Still, adding other materials such as cement or lime is necessary to increase the carrying capacity and meet the set specifications